Thwarted belongingness and empathy's relation with organizational culture change - de Grandpré, Éloïse; Suurd Ralph, Cindy; Hiller, Emily (Frontiers in Psychology, 2024)
Introduction In response to several high-profile cases of senior leaders in the Canadian Armed Forces (CAF) being accused of various forms of sexual and professional misconduct, the organization has committed to culture change. Drawing on the group engagement model and empirical evidence, we propose that CAF members' experience of thwarted belongingness reduces their capacity to show empathy, which in turn affects their support for culture change. Method Participants were 139 Naval and Officer Cadets from the Royal Military College of Canada who were predominantly male (61%), between 18 and 21 years old (80%), and not members of a visible minority group (68%). Data was collected via an online self-report survey assessing thwarted belongingness, empathy, and attitudes toward culture change. Results Whether participants experienced thwarted belongingness was not directly related to their level of support for culture change. Individuals' thwarted belongingness was indirectly and negatively associated with support for culture change, through its impact on empathy. Discussion Taken together, the results demonstrate that cadets' experience of belongingness contributed to their level of empathy, which together predicted their support for culture change initiatives. Efforts to change the culture of the CAF may need to consider improving members' levels of belongingness and, by extension, their levels of empathy. Implications for inclusion efforts are discussed.